RED: Redundancy-driven data extraction from result pages? - Guo, J; Crescenzi, V; Furche, T; Grasso, G; Gottlob, G (Association for Computing Machinery, 2019)
Data-driven websites are mostly accessed through search interfaces. Such sites follow a common publishing pattern that, surprisingly, has not been fully exploited for unsupervised data extraction yet: the result of a search is presented as a paginated list of result records. Each result record contains the main attributes about one single object, and links to a page dedicated to the details of that object. We present red, an automatic approach and a prototype system for extracting data records from sites following this publishing pattern. red leverages the inherent redundancy between result records and corresponding detail pages to design an effective, yet fully-unsupervised and domain-independent method. It is able to extract from result pages all the attributes of the objects that appear both in the result records and in the corresponding detail pages. With respect to previous unsupervised methods, our method does not require any a priori domain-dependent knowledge (e.g, an ontology), can achieve a significantly higher accuracy while automatically selecting only object attributes, a task which is out of the scope of traditional fully unsupervised approaches. With respect to previous supervised or semi-supervised methods, red can reach similar accuracy in many domains (e.g., job postings) without requiring supervision for each domain, let alone each website.